2022
DOI: 10.1007/s11427-021-2070-y
|View full text |Cite
|
Sign up to set email alerts
|

A urinary proteomic landscape of COVID-19 progression identifies signaling pathways and therapeutic options

Abstract: Signaling pathway alterations in COVID-19 of living humans as well as therapeutic targets of the host proteins are not clear. We analyzed 317 urine proteomes, including 86 COVID-19, 55 pneumonia and 176 healthy controls, and identified specific RNA virus detector protein DDX58/RIG-I only in COVID-19 samples. Comparison of the COVID-19 urinary proteomes with controls revealed major pathway alterations in immunity, metabolism and protein localization. Biomarkers that may stratify severe symptoms from moderate on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…ATP5C1 , ATP5H ). These data are coherent with recent findings in which several authors demonstrated metabolic reprogramming also at the level of both TCA ( Barberis et al, 2020 ) ( Liu et al, 2022 ) and oxidative phosphorylation ( Santos et al, 2021 ), leading to an impairment of ATP synthesis and the contemporary activation of anaerobic metabolic pathways induced by SARS-CoV-2 infection ( Jamison et al, 2022 ). To the best of our knowledge, for the first time, our data suggest a possible role of the Spike S1 subunit in physically mediating these phenomena.…”
Section: Resultssupporting
confidence: 92%
“…ATP5C1 , ATP5H ). These data are coherent with recent findings in which several authors demonstrated metabolic reprogramming also at the level of both TCA ( Barberis et al, 2020 ) ( Liu et al, 2022 ) and oxidative phosphorylation ( Santos et al, 2021 ), leading to an impairment of ATP synthesis and the contemporary activation of anaerobic metabolic pathways induced by SARS-CoV-2 infection ( Jamison et al, 2022 ). To the best of our knowledge, for the first time, our data suggest a possible role of the Spike S1 subunit in physically mediating these phenomena.…”
Section: Resultssupporting
confidence: 92%
“…While most published studies analyzed in this research area have focused on the following specimen types: blood samples, including serum [11][12][13][14][15][16][17][18][19][20][21] , plasma 12,13,[22][23][24][25][26][27][28][29][30][31][32] , and peripheral blood mononuclear cells (PBMC) 33,34 , there are also studies analyzing FFPE tissue 35,36 , urine [37][38][39][40][41] , fecal 42 , sputum 23 , extracellular vesicle 43,44 , cerebrospinal fluid 21 , semen 45 , colostrum 46 , colostrum 47 and nasopharynx swabs samples 48 . All these studies have provided proteomic snapshots of different aspects of tissues from COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that SARS-CoV-2 could directly infect the kidney via ACE2, TMPRSS2, and CD147 molecules, contributing to the development of acute kidney injury. Studies have indicated that 10% to 22% of men in the acute infection phase of COVID-19 could develop orchitis or epididymitis, and another research discovered SARS-CoV-2 in testicular tissue specimens of dead patients with COVID-19 through transmission electron microscopy, suggesting that testicular inflammation caused by COVID-19 may be attributable to the direct invasion of SARS-CoV-2[ [34] , [35] , [36] ]. Another study claimed that SARS-CoV-2 was not found in the semen of individuals recovering from COVID-19, but it could not completely exclude the possibility that SARS-CoV-2 was present in semen fluid during acute infection accompanied severe manifestations of COVID-19[ 37 ].…”
Section: Discussionmentioning
confidence: 99%